Investigación experimental de una serie asociativa de zoonimos en lenguas de diferente estructura: sobre el material de las lenguas rusa, francesa y cabardiano-circasiana - Guketlova, Fátima N. (Cuadernos de Rusística Española, 2012)
Zoomorphic culture codes revealing the system of symbols and standards of a national culture are able to bring about specifi c characters of world perception inherent to language and culture earners. The existence of such codes is universal. However, while maintaining universal features, these codes still have unique national peculiarities. What we are interested in is the nation-related specifi city of choice of expressive means – a human in ani-morphologic language units containing a typical, image-bearing, easily interpreted behavioural sign purporting to animals.